Persepsi Mahasiswa Terhadap Pembelajaran Daring Matematika Ideal Di Masa Pandemi Covid-19 - Takaendengan, Bertu Rianto; Asriadi, Asriadi (Universitas Muslim Indonesia, 2021)
This study aims to determine student perceptions of the ideal mathematics learning during the covid-19 pandemic. This research is a qualitative descriptive study which was carried out using observation, questionnaire and interview techniques to 36 students of mathematics education class 2020 Gorontalo State University Â who had participated in online learning for 2 semesters. The results showed that mathematics learning carried out during the covid-19 pandemic was still not ideal with a percentage of 91.6% due to the nature of difficult and abstract mathematics material and there were several repeated obstacles that occurred in the online learning process, namely: 1) teachers were less proficient in use of online platforms; 2) teaching is carried out using only sound (audio); 3) the internet network is less stable so that students cannot participate in online learning. The recommendations for the ideal mathematics learning are: 1) in the online learning process the teacher must be able to master (proficiently) use the online platform used; 2) teachers must be able to design innovative and fun learning by utilizing the features available on the platform or utilizing objects that are around students; 3) teachers can provide learning resources that can be accessed at any time so as to facilitate students in order not to miss the subject matter.